Total Quality Management Practices and Adoption in Construction Industry Organizations: A Review - Alawag, A.M. (Institute of Electrical and Electronics Engineers Inc., 2020)
Total Quality Management (TQM) practices are well-known to encourage the performance of organizations in terms of procedures, services, and products to meet customers' expectations. TQM plays a critical role in developing products as well as other developments in the arena of construction industry organizations. This paper reviews the concept of TQM, benefits and connection between TQM and project performance in construction organizations. The reviewed studies focused on practices and adoption of quality through implementing TQM in the construction industry and its suitable applications in the various phases of the construction project. The concept of TQM mostly facilitates attaining continual performance improvements in order to sustain business excellence. This study contributes to the science and knowledge on TQM and project performance by delivering theoretical significance on TQM ability to improve the performance of the construction industry. Numerous studies have recommended the practices and adoption of TQM are likely to enhance a company's performance. This paper has further identified some benefits of TQM such as improvement in product quality, increased customer satisfaction, and continues improvement towards world-class organizations and achieve the customers' needs and expectations successfully. Â© 2020 IEEE.